2020
DOI: 10.1098/rspb.2020.0713
|View full text |Cite
|
Sign up to set email alerts
|

Androgen-dependent sexual dimorphism in pituitary tryptophan hydroxylase expression: relevance to sex differences in pituitary hormones

Abstract: Serotonin is a biogenic monoamine conserved across phyla that is implicated in diverse physiological and behavioural functions. On examining the expression of the rate-limiting enzymes in serotonin synthesis, tryptophan hydroxylases (TPHs), in the teleost medaka ( Oryzias latipes ), we found that males have much higher levels of tph1 expression as compared with females. This robust sexual dimorphism was found to probably result from the direct stimulation of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
15
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(29 citation statements)
references
References 47 publications
7
15
0
1
Order By: Relevance
“…For instance, we show for the first time that tshba -expressing cell volumes are the largest in adult females, and pomca -expressing cell volumes are the largest in adult males. Our qPCR data on tshba and pomca levels agree with a previous study in medaka ( 60 ) and further support the sexual dimorphism. In that study, androgens were shown to stimulate transcription of tph1 , which encodes an enzyme required for serotonin synthesis, in pomc -expressing cells.…”
Section: Discussionsupporting
confidence: 91%
“…For instance, we show for the first time that tshba -expressing cell volumes are the largest in adult females, and pomca -expressing cell volumes are the largest in adult males. Our qPCR data on tshba and pomca levels agree with a previous study in medaka ( 60 ) and further support the sexual dimorphism. In that study, androgens were shown to stimulate transcription of tph1 , which encodes an enzyme required for serotonin synthesis, in pomc -expressing cells.…”
Section: Discussionsupporting
confidence: 91%
“…We also observed sexual dimorphism of fshb and lhb mRNA levels in adults, in agreement with a previous medaka study (56). This suggests a difference in gonadotrope cell activity as we did not observe a difference in population size, also supported by the absence of significant differences in Lh or Fsh cell numbers in previous studies (9,63).…”
Section: Sexual Dimorphism Of Tshba-and Pomca-expressing Cell Populationssupporting
confidence: 93%
“…For instance, we show for the first time that tshba-and pomca-expressing cell populations are more numerous in adult females and males, respectively. Our qPCR data on tshba and pomca levels agree with previous studies in medaka (56) and further support the sexual dimorphism. In the previous medaka study, androgens were suggested to be involved in tshb suppression in adult males via activation of tph1 transcription expressed in pomc-expressing cells.…”
Section: Sexual Dimorphism Of Tshba-and Pomca-expressing Cell Populationssupporting
confidence: 90%
“…Previous postmortem analysis of brain tissues reported that TPH2 mRNA expression is abundant in the dorsal raphe nucleus, median raphe nucleus, and raphe nuclei-containing regions such as pons and medullar, not the pituitary gland [35,36]. Although TPH1 is mainly expressed in peripheral tissues, some papers have already reported the existence of TPH1 in the brain, especially in the pituitary gland [37][38][39]. Our results showed that the pituitary gland expressed TPH1 as well as TPH2, and the expression levels were higher Previous postmortem analysis of brain tissues reported that TPH2 mRNA expression is abundant in the dorsal raphe nucleus, median raphe nucleus, and raphe nuclei-containing regions such as pons and medullar, not the pituitary gland [35,36].…”
Section: Tph Expression In Human Tissuementioning
confidence: 99%